About the need to replace pumping equipment or impellers of main pumps when pumping capacity of oil and petroleum products changes - V. V. Shalay; M. O. Myznikov; M. I. Gildebrandt; E. V. Khodoreva (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article presents the results of a study related to determining the need to replace pumping equipment or impellers of main pumps to increase efficiency while reducing pumping volumes. Calculations are carried out on the example of a technological section of a specific oil pipeline. The paper demonstrates an approach to assessing the economic feasibility of replacing pumping equipment or upgrading it in conditions of changing transportation volumes. The calculation method can be applied to any oil pipelines and product pipelines.